2020
DOI: 10.5194/wcd-1-597-2020
|View full text |Cite
|
Sign up to set email alerts
|

How an uncertain short-wave perturbation on the North Atlantic wave guide affects the forecast of an intense Mediterranean cyclone (Medicane Zorbas)

Abstract: Abstract. Mediterranean cyclogenesis is known to be frequently linked to ridge building over the North Atlantic and subsequent anticyclonic Rossby wave breaking over Europe. But understanding of how this linkage affects the medium-range forecast uncertainty of Mediterranean cyclones is limited, as previous predictability studies have mainly focused on the relatively rare cases of Mediterranean cyclogenesis preceded by upstream extratropical transition of tropical cyclones. This study exploits a European Centre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 60 publications
6
27
0
Order By: Relevance
“…Such PV streamers and cutoffs can favour EPE formation through inducing enhanced moisture transport and forcing for ascent via reduced static stability beneath the positive upper tropospheric PV anomaly and dynamical lifting ahead (Funatsu and Waugh, 2008;Schlemmer et al, 2010). Accordingly, many case studies have linked Rossby wave breaking to EPEs in several regions, including, but not limited to, southwestern North America, northwestern Africa, the Alpine region, the Mediterranean, southern Africa, the Middle East, Pakistan and the Himalayas, and East Asia (Massacand et al, 1998;Knippertz andMartin, 2005, 2007;Argence et al, 2006;Hart et al, 2010;Martius et al, 2013;De Vries et al, 2016;Vellore et al, 2016;Tsuji and Takayabu, 2019;Portmann et al, 2020b). Systematic climatological analyses, however, are limited to the Alpine region (Martius et al, 2006), the Middle East (De Vries et al, 2018), South Africa (Favre et al, 2013), and North America (Abatzoglou, 2016;Barbero et al, 2019;Moore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such PV streamers and cutoffs can favour EPE formation through inducing enhanced moisture transport and forcing for ascent via reduced static stability beneath the positive upper tropospheric PV anomaly and dynamical lifting ahead (Funatsu and Waugh, 2008;Schlemmer et al, 2010). Accordingly, many case studies have linked Rossby wave breaking to EPEs in several regions, including, but not limited to, southwestern North America, northwestern Africa, the Alpine region, the Mediterranean, southern Africa, the Middle East, Pakistan and the Himalayas, and East Asia (Massacand et al, 1998;Knippertz andMartin, 2005, 2007;Argence et al, 2006;Hart et al, 2010;Martius et al, 2013;De Vries et al, 2016;Vellore et al, 2016;Tsuji and Takayabu, 2019;Portmann et al, 2020b). Systematic climatological analyses, however, are limited to the Alpine region (Martius et al, 2006), the Middle East (De Vries et al, 2018), South Africa (Favre et al, 2013), and North America (Abatzoglou, 2016;Barbero et al, 2019;Moore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Portmann et al . (2020) showed that the uncertain position of a PV streamer was critical for the proper simulations of the September 2018 medicane, extending current knowledge on the role of upstream uncertainties in medium‐range predictability.…”
Section: Introductionmentioning
confidence: 78%
“…Although the complex topography of the region traversed by the October 1996 vortex makes the interpretation of the results for this case less straightforward, the simulations in both cases agree that the reduced humidity inhibits the development of the two cyclones. The presence of dry intrusions in many (if not all) medicanes described in literature (e.g., Cioni et al ., 2016; Carrió et al ., 2017; Miglietta et al ., 2017; Portmann et al ., 2020) and the reduction in convective activity and rainfall observed after the upper‐level dry air has reached the cyclone core (e.g., Claud et al ., 2010; Miglietta et al ., 2013; Dafis et al ., 2018; Marra et al ., 2019) suggest the generality of these results. However, further cases need to be examined before reaching more definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations